Chronic inflammatory demyelinating polyradiculoneuropathy: from pathology to phenotype. Issue 9 (12th February 2015) - Mathey, Emily K; Park, Susanna B; Hughes, Richard A C; Pollard, John D; Armati, Patricia J; Barnett, Michael H; Taylor, Bruce V; Dyck, P James B; Kiernan, Matthew C; Lin, Cindy S-Y
Abstract : Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is an inflammatory neuropathy, classically characterised by a slowly progressive onset and symmetrical, sensorimotor involvement. However, there are many phenotypic variants, suggesting that CIDP may not be a discrete disease entity but rather a spectrum of related conditions. While the abiding theory of CIDP pathogenesis is that cell-mediated and humoral mechanisms act together in an aberrant immune response to cause damage to peripheral nerves, the relative contributions of T cell and autoantibody responses remain largely undefined. In animal models of spontaneous inflammatory neuropathy, T cell responses to defined myelin antigens are responsible. In other human inflammatory neuropathies, there is evidence of antibody responses to Schwann cell, compact myelin or nodal antigens. In this review, the roles of the cellular and humoral immune systems in the pathogenesis of CIDP will be discussed. In time, it is anticipated that delineation of clinical phenotypes and the underlying disease mechanisms might help guide diagnostic and individualised treatment strategies for CIDP.